2021
DOI: 10.3390/diagnostics11010119
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of F18-FDG PET/CT in Male Breast Cancers Patients

Abstract: Introduction: F18-FDG PET/CT is the most important hybrid imaging used in the diagnostic, staging, follow-up, and treatment evaluation response in cancer patients. However, it is well-known that in breast cancer the use of F18-FDG is not included in the first line protocol of initial diagnostic, both in female and male breast cancer patients. F18-FDG PET/CT is a valuable tool to provide information on extra-axillary lymph node involvement, distant metastases, and other occult primary cancers. This study assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(36 citation statements)
references
References 20 publications
0
36
0
Order By: Relevance
“…The incidence of stage III/IV cancer at admission is >60% in Africa, <40% in North America and Western European countries, and between 40% and 60% in Eastern Europe and South America. The reasons for admission at later stages are reported to be race, low socioeconomic status, lack of awareness about the disease, and uncertainties in the characterization of highrisk patients for screening in the literature 8,[11][12][13][14][15][16][17] . In our study, the most common symptom was a breast mass, and 50% of them were at late stages at the time of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of stage III/IV cancer at admission is >60% in Africa, <40% in North America and Western European countries, and between 40% and 60% in Eastern Europe and South America. The reasons for admission at later stages are reported to be race, low socioeconomic status, lack of awareness about the disease, and uncertainties in the characterization of highrisk patients for screening in the literature 8,[11][12][13][14][15][16][17] . In our study, the most common symptom was a breast mass, and 50% of them were at late stages at the time of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…This review is not without some limitations that can affect its quality: low sample of studies considered, high heterogeneity of patients and different setting for the use of 18 F-FDG PET/CT are the most relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding diagnostic performances of hybrid imaging for the assessment of MCB, data reported in literature revealed a sensitivity ranging from 95% to 100%, a specificity ranging from 80% to 67%, a PPV ranging from 91% to 86%, an NPV ranging from 89% to 100% and an accuracy ranging from 90% to 100%, depending on the study considered [21,22]. Several studies demonstrated the role of 18 F-FDG PET/CT for the initial assessment of MBC. In this setting, its utility was underlined in particular for the evaluation of the primary site of the disease and to reveal the presence of axillary and locoregional or distant nodal metastasis.…”
Section: F-fdg Pet/ct For the Initial Staging Of Male Breast Cancermentioning
confidence: 99%
See 2 more Smart Citations